Moving beyond the Book List: Building a Pediatric Responsive Library Program. Issue 1 (2nd January 2022) - Taylor, Natalie Greene; Shereff, Denise; Baum, Brittany; Chan, Janet; Cannon, Peter
ABSTRACT: This article discusses the design and implementation of a pediatric library program in a short-term, in-patient, acute care behavioral health facility in Pasco County, FL. The collection was built initially with resources already held by the University of South Florida's (USF) School of Information (SI), with additional resources acquired through financial support from the Southeastern/Atlantic Region of the Network of the National Library of Medicine and the School of Information's Dr. Henrietta M. Smith Youth Services Fund. For this unique project, the USF SI Responsive Librarianship Lab researchers established both a physical library and an ongoing group session health literacy program at the facility.